ANALISIS TINGKAT STRES MAHASISWA TERHADAP PEMBELAJARAN DARING PADA MATA KULIAH STATISTIK BISNIS DI PENDIDIKAN VOKASI - Hutomo Atman Maulana; Rosada Dwi Iswari (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTThis study aimed to analyze undergraduate student’s stress level due to onlinelearning of statistics for business course at vocational education during the coronavirus pandemic (COVID-19). This research was a qualitative descriptive study. Thepopulation in this study was all of the students of the Applied Undergraduate ProgramDepartment of International Business Administration of Politeknik Negeri Bengkalis.The samples were taken by using purposive sampling techniques that only focused onstudents who where taking statistics for business course since enacted online learningdue to the COVID-19 pandemic. The data was collected by using onlinequestionnaires and in -depth interviews with the students to get more detailedinformation. The data analysis technique used in this study was a a qualitativeanalysis consisting of data collection, data reduction, data presentation, andconclusion. The result showed that online learning of statistics for business coursecaused 3% of the student having stress level in extremely severe categories, 13% insevere categories, 8% in moderate categories, 24% in mild categories, and 52% innormal categories. The stress level experienced by student were influenced by thegender, while the age of the students under range of 17 -20 years old did not affectstress levels.Keywords: undergraduate student’s stress level, online learning, vocational education.